Exploring the regulatory role of lncRNA in cancer immunity - Zhan, Dan-ting; Xian, Hong-chun (Frontiers in Oncology, 2023)
Imbalanced immune homeostasis in cancer microenvironment is a hallmark of cancer. Increasing evidence demonstrated that long non-coding RNAs (lncRNAs) have emerged as key regulatory molecules in directly blocking cancer immunity cycle, apart from activating negative regulatory pathways for restraining tumor immunity. LncRNAs reshape tumor microenvironment via recruitment and activation of innate and adaptive lymphoid cells. In this review, we summarized the versatile mechanisms of lncRNAs implicated in cancer immunity cycle, including inhibition of antitumor Tcell activation, blockade of effector T-cell recruitment, disruption of T-cell homing, and recruitment of immunosuppressive cells, and inducing an imbalance between antitumor effector cells (cytotoxic T lymphocytes,M1 macrophages, and T helper type 1 cells)versus immunosuppressive cells (M2 macrophages, T helper type 2 cells ,myeloid derived suppressor cells, and regulatory T cells)that infiltrate in the tumor. As such, we would highlight the potential of lncRNAs as novel targets for immunotherapy.